Chemical seed priming influence on the field performance of rapeseed-mustard genotypes in Indo-Gangetic plains of West Bengal - Rupa Das; Saikat Biswas; Amitava Dutta (Discover Agriculture)
Abstract Enhancing oilseed production with quality seeds of improved varieties is a crucial task given the current demand-supply imbalance. It can be resolved, and rapeseed-mustard productivity can be increased in the Indo-Gangetic plains of West Bengal by developing the genotypes that are adapted to certain agroclimatic conditions and improving seed quality using regulated pre-sowing hydration methods, or seed priming. Therefore, to assess the performance of six rapeseed-mustard genotypes under various seed priming treatments, a two-year field study was carried out at the District Seed Farm, Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, during the winter seasons of 2017–18 and 2018–19. Five priming treatments, including a control (no priming), were employed in the split-plot trial, which was replicated three times. The rapeseed variety ‘Anushka’ did the worst among the genotypes, whereas the mustard variety ‘Pusa Bold’ showed the best growth, yield attributes, and seed production (1829.6 kg ha−1). Seed priming—especially with chemical agents like KH2PO4 and KNO3—significantly increased growth and yield compared to hydro-priming or the control. Notably, ‘Pusa Bold’ produced a seed yield of 2088.6 kg ha−1 when primed with KH2PO4 or KNO3, with net returns of $2008 per hectare. Crop performance was also enhanced with PEG-6000. Therefore, seed priming of mustard genotype ‘Pusa Bold’ with KNO3, KH2PO4, or PEG-6000 can be recommended for successful oilseed cultivation in the Indo-Gangetic plains of West Bengal.